Composite material capable of keeping golden appearance of basalt fiber as well as preparation method and application of composite material
By preparing a composite material containing a transparent thermoplastic film and nano-silicon oxide aerogel on the basalt fibers, the problem that the color of the basalt fibers cannot be retained after resin composite is solved, and the long-term maintenance of the golden appearance and the high performance of the composite material are achieved.
Patent Information
- Application Number
- CN202411674315.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
After being compounded with the resin, basalt fibers often cannot retain their original golden color, resulting in a decline in commercial value.
A composite structure is adopted, including a basalt golden appearance layer, an adhesive dielectric layer and a body material. The golden appearance layer of basalt is composed of basalt fibers and transparent thermoplastic films. The thermoplastic films include PE, PP, PET, PC, TPU and other materials, nano-silica aerogel and silicone oil, and are prepared by hot pressing composite technology.
Effectively maintain the golden appearance of basalt fibers, improve the mechanical properties and durability of composite materials, while reducing the environmental impact and cost of the preparation process.
Smart Images

Figure CN119502475A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a composite material that maintains the golden appearance of basalt fiber and a preparation method and application thereof. Background Art
[0002] Basalt fiber is a continuous fiber made by melting natural basalt stone at 1450℃~1500℃ and then drawing it at high speed through a platinum-rhodium alloy drawing plate. Basalt continuous fiber not only has high strength, but also has many excellent properties such as electrical insulation, corrosion resistance, and high temperature resistance. It is a new type of inorganic environmentally friendly green high-performance fiber material with broad application prospects. The color of basalt fiber is generally golden brown with a good golden luster. For many application scenarios with appearance requirements, such as automotive interior and exterior trim, shoes, bags, etc., it is hoped that the golden appearance of basalt fiber will be retained as a selling point of the product, which has good commercial value.
[0003] During the processing of basalt fiber, in order to improve its functionality and applicability and make it easier to process and shape, it is often necessary to compound it with some polymer materials, such as resin. However, after compounding with resin, basalt fiber often cannot retain its original color, resulting in a decrease in its commercial value. After analysis, there are two reasons why the color of basalt fiber cannot be well displayed: one is that the color produced during the processing is covered; the other is the discoloration caused by the infiltration of organic resins and other substances.
[0004] Relevant studies have proposed corresponding solutions to this problem and achieved certain results. For example, patent CN202311512469A discloses a basalt fiber anti-discoloration water-based coating, preparation method and basalt fiber products. By applying polyurethane coating on the surface of basalt fiber material, it better solves the discoloration problem caused by basalt fiber being infiltrated by polyurethane resin. Although this method solves the problem of basalt fiber color retention, its surface treatment process is not environmentally friendly, and the treatment cost is too high. It cannot be applied to different resin systems. Long-term use may still cause fading problems, which limits the application and promotion of basalt fiber. Summary of the invention
[0005] The embodiments of the present application provide a composite material for maintaining the golden appearance of basalt fiber and a preparation method and application thereof, so as to solve the problem in the related art that the golden appearance of basalt fiber cannot be well preserved when it is used.
[0006] In a first aspect, a composite material for maintaining the golden appearance of basalt fiber is provided, comprising:
[0007] A basalt golden appearance layer, the basalt golden appearance layer comprises basalt fiber and a thermoplastic film, and the polymer composite film layer is arranged on the surface of the basalt fiber;
[0008] A bonding medium layer, one side of which is bonded to the surface of the basalt gold appearance layer by an adhesive.
[0009] Furthermore, the thickness of the basalt golden appearance layer is 0.2-1 mm; the thickness can be adjusted as needed.
[0010] Furthermore, the thickness of the adhesive medium layer is 0.05-0.2 mm; the thickness of the adhesive medium layer can be adjusted according to actual needs.
[0011] Furthermore, the thermoplastic film includes at least one of PE, PP, PET, PC, and TPU; such material is colorless and transparent, which is beneficial to reduce the obstruction of the color of the basalt itself.
[0012] Furthermore, the thickness of the thermoplastic film is 0.05-0.2 mm; the thickness of the thermoplastic film can be adjusted as needed.
[0013] Furthermore, the thermoplastic film also includes nano-silicon oxide aerogel and silicone oil;
[0014] Nano-silica aerogel has a unique porous structure. Its porous structure and high specific surface area can become an obstacle to the movement of resin molecular chains, affecting the arrangement and stacking process of resin molecular chains, and helping to reduce the discoloration of thermoplastic materials and the shading of basalt color after discoloration;
[0015] Silicone oil can improve the fluidity and flexibility of resin, and can also improve the processability of resin by changing the viscosity of resin. It can also improve the viscosity of thermoplastic materials, thereby enhancing the composite strength of thermoplastic materials and adhesive media, and improve the mechanical properties of the prepared composite materials.
[0016] The addition of silicone oil can also improve the gloss and transparency of the prepared composite material, and improve the touch of the composite material.
[0017] Furthermore, the silicone oil is a modified silicone oil, including at least one of amino-modified silicone oil, epoxy-modified silicone oil or polyether-modified silicone oil.
[0018] The modified silicone oil has a special group and has strong activity, which can better adjust the viscosity of the thermoplastic material, control the fluidity of the thermoplastic material after hot pressing, and can better improve the viscosity and processing performance of the thermoplastic material.
[0019] Furthermore, the bonding medium layer is non-woven fabric or fiber felt;
[0020] Optionally, the non-woven fabric is PP or PET non-woven fabric, and the fiber felt is glass fiber felt or aramid fiber felt; other non-woven fabrics or fiber felts or other materials may also be selected according to performance and functional requirements.
[0021] Furthermore, the binder is a resin; optionally, the resin may be a thermosetting resin or a thermoplastic resin.
[0022] Furthermore, the thermosetting resin is selected from at least one of epoxy resin, polyurethane and unsaturated resin.
[0023] Furthermore, the thermoplastic resin is selected from at least one of PP, PA, PC and PET.
[0024] In a second aspect, the present invention provides a composite material, comprising the composite material with a golden appearance and a main body material, wherein the composite material with a golden appearance is arranged on the surface of the main body material.
[0025] Furthermore, the composite material with a golden appearance is arranged on the surface of the main material through the adhesive medium layer.
[0026] Furthermore, the main body material is a thermoplastic material or a thermosetting material.
[0027] Furthermore, when the main material is a thermosetting material, the composite material also includes hot melt adhesive; optionally, the hot melt adhesive is a hot melt adhesive film or a hot melt adhesive powder, and the hot melt adhesive film includes at least one of PP adhesive film, PA adhesive film, and EVA adhesive film; the hot melt adhesive powder includes at least one of PP powder, PA powder, and EVA powder.
[0028] Furthermore, the thickness of the hot melt adhesive film is 0.05-0.2 mm. The thickness of the hot melt adhesive film can be adjusted according to actual needs.
[0029] Furthermore, the hot melt adhesive is arranged between the main body material and the adhesive medium layer to play a bonding role.
[0030] In a third aspect, the present application provides a method for preparing a composite material that maintains the golden appearance of basalt fiber, comprising the following steps:
[0031] Step 1: Laying a thermoplastic material on the surface of the basalt fiber material for hot pressing and compounding to prepare a basalt golden appearance layer with a golden appearance;
[0032] Step 2: Lay a bonding medium layer on one surface of the obtained basalt golden appearance layer, and then perform hot pressing and lamination to obtain the composite material with golden appearance.
[0033] Furthermore, the thermoplastic material is a thermoplastic film; the thermoplastic film includes at least one of a PE film, a PP film, a PET film, a PC film, and a TPU film.
[0034] Furthermore, the thermoplastic material is thermoplastic powder; the thermoplastic film comprises at least one of PE powder, PP powder, PET powder, PC powder and TPU powder.
[0035] In a fourth aspect, the present application provides a method for preparing a composite material that maintains the golden appearance of basalt fiber, wherein one side of the composite material having the adhesive medium layer is laid on a base material for hot pressing and compounding to obtain the composite material.
[0036] Further, the main body material is a thermoplastic material or a thermosetting material;
[0037] Furthermore, when the main body material is a thermosetting material, it also includes laying a layer of hot melt adhesive between the side of the composite material with the bonding medium layer and the main body material;
[0038] Furthermore, the thermoplastic material other than the main body material is obtained by mixing thermoplastic resin, silicone aerogel and silicone oil in a mass ratio of 80-90:1-4:4-8.
[0039] When the amount of silica aerogel added is within this range, it can better ensure that the thermoplastic material can form a film with good transparency on the surface of the basalt fiber;
[0040] When the amount of silicone oil added is within this range, the thermoplastic material can have better processing performance on the basis of better increased transparency and color retention performance;
[0041] When the amount of silicone oil added is within this range, the material can have a higher viscosity. The specific silicone oil used in the present application can increase the viscosity and fluidity of the thermoplastic material in a flowing state, thereby increasing the viscosity. When a larger amount is added, the viscosity will be reduced instead.
[0042] In a fifth aspect, the present application provides an automotive interior component, comprising the composite material provided above.
[0043] In a sixth aspect, the present application provides a bag material, including the composite material provided above.
[0044] The beneficial effects of the technical solution provided by this application include:
[0045] 1. The composite material provided in the present application can improve the discoloration problem because its composite material layer with a golden appearance contains a transparent thermoplastic material. Therefore, the golden appearance of the basalt fiber can be well maintained for a long time, which is conducive to the promotion and application of basalt fiber in the fields of automotive interiors, luggage, etc.;
[0046] 2. The preparation method of the composite material provided by the present invention improves the problems of discoloration and poor composite strength by adding thermoplastic materials, and controls the process conditions during the preparation process to improve the discoloration problem. The composite material finally prepared has good mechanical properties and good durability while maintaining the basalt gold appearance; it also has the advantages of environmentally friendly preparation process and simple preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0048] Figure 1 A schematic diagram of the structure of the composite material provided in Example 6 of the present application;
[0049] Figure 2 This is an appearance diagram of the composite material provided in Example 5 of the present application after being placed for 3 months.
[0050] Explanation of the accompanying drawings: 1. Basalt golden appearance layer; 2. Adhesive medium layer; 3. Main body material. DETAILED DESCRIPTION
[0051] The technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
[0052] The amino-modified silicone oil involved in the examples and comparative examples of the present application is manufactured by Wacker Chemicals, with a model of HDK H 207; the epoxy-modified silicone oil is manufactured by Dow Corning, with a model of Dow Corning EP 4850; the polyether-modified silicone oil is manufactured by Schlumberger, with a model of KS 660. The ordinary silicone oil is manufactured by Dow Corning, with a model of DC200 fluid, 350cs.
[0053] Examples 1-5 and Comparative Examples 1-2
[0054] Preparation of composite materials with golden appearance:
[0055] Step 1: Laying a thermoplastic material (the thermoplastic material includes thermoplastic resin, silicon aerogel and silicone oil) on the surface of the basalt fiber material for hot pressing and compounding to prepare a basalt golden appearance layer with a golden appearance;
[0056] Step 2: Lay an adhesive medium layer on one surface of the obtained basalt golden appearance layer, and then perform hot pressing and compounding to obtain the composite material with golden appearance.
[0057] The parameter settings in Examples 1-4 and Comparative Example 1 are shown in Table 1:
[0058] Table 1
[0059]
[0060] Embodiment 6-8
[0061] Preparation of composite materials:
[0062] The composite materials obtained in Examples 1-3 were placed on the main material on one side with the bonding medium layer and hot pressed to obtain composite materials, corresponding to Examples 6-8. The materials and parameter settings in Examples 6-8 are shown in Table 2. The schematic diagram of the composite material structure obtained in Example 6 is shown in Figure 1 .
[0063] Table 2
[0064]
[0065]
[0066] Example 9
[0067] Preparation of composite materials:
[0068] The side of the composite material obtained in Example 4 with the bonding medium layer was laid on the carbon fiber reinforced epoxy resin composite material for hot pressing (conditions: 5 MPa, 180° C., hot pressing for 3 min) to obtain a composite material.
[0069] Example 10
[0070] Preparation of composite materials:
[0071] The side of the composite material obtained in Example 5 with the bonding medium layer was laid on the carbon fiber reinforced epoxy resin composite material for hot pressing (conditions: 5 MPa, 180° C., hot pressing for 3 min) to obtain a composite material.
[0072] Comparative Example 3
[0073] Preparation of composite materials:
[0074] The side of the composite material obtained in Comparative Example 1 with the bonding medium layer was laid on the carbon fiber reinforced epoxy resin composite material for hot pressing (conditions: 5 MPa, 180° C., hot pressing for 3 min) to obtain a composite material.
[0075] Comparative Example 4
[0076] Preparation of composite materials:
[0077] The side of the composite material obtained in Comparative Example 2 with the bonding medium layer was laid on the main material (carbon fiber reinforced epoxy resin composite material) and hot-pressed (conditions: 5 MPa, 180° C., hot pressing for 3 min) to obtain a composite material.
[0078] Performance Testing
[0079] The properties of the composite materials prepared in Examples 6-9 and Comparative Examples 3-6 were tested, and the test results are shown in Table 3. And, wherein:
[0080] The test method of tensile strength is tested in accordance with GB / T 1447-2005 standard;
[0081] The test method for impact toughness is tested in accordance with GB T2567-2008 standard.
[0082] Table 3
[0083] Tensile strength(MPa) <![CDATA[Impact toughness (KJ / m 2 )]]> Appearance Color Example 6 270.8 41.3 gold Example 7 271.6 42.4 gold Example 8 251.9 38.9 gold Example 9 268.3 39.7 Partially brown Example 10 239.6 30.4 Partially brown Comparative Example 3 242.1 34.9 gold Comparative Example 4 262.2 38.1 brown
[0084] It can be seen from Table 3 that the composite material prepared by the method of the present invention can maintain the golden appearance of basalt while having good mechanical properties and good application prospects; in Example 5, ordinary silicone oil is added, but since it does not contain active groups, the viscosity of the thermoplastic material is poor, and the mechanical properties of the composite material with a body prepared using it are poor.
[0085] In addition, the composite material prepared in Example 5 also has a good golden appearance. However, after the composite material prepared in Example 5 is placed for three months, its golden appearance part turns brown. Figure 2 .
Claims
1. A composite material maintaining the golden appearance of basalt fiber, characterized in that: include: A basalt golden appearance layer, the basalt golden appearance layer comprising basalt fiber and a thermoplastic film, wherein the thermoplastic film is arranged on the surface of the basalt fiber; A bonding medium layer, one side of which is bonded to the surface of the basalt gold appearance layer by an adhesive.
2. The composite material for maintaining the golden appearance of basalt fiber according to claim 1, characterized in that: The thermoplastic film includes PE, PP, PET, PC, and TPU.
3. The composite material for maintaining the golden appearance of basalt fiber according to claim 2, characterized in that: The thermoplastic film also includes nano silicon oxide aerogel and silicone oil.
4. The composite material for maintaining the golden appearance of basalt fiber according to claim 1, characterized in that: The bonding medium layer is non-woven fabric or fiber felt.
5. The composite material for maintaining the golden appearance of basalt fiber according to claim 1, characterized in that: The adhesive is resin.
6. The composite material for maintaining the golden appearance of basalt fiber according to claim 3, characterized in that: The silicone oil is at least one of amino-modified silicone oil, epoxy-modified silicone oil or polyether-modified silicone oil.
7. A composite material maintaining the golden appearance of basalt fiber, characterized in that: The composite material comprises a main body material and the composite material with a golden appearance according to any one of claims 1 to 6, wherein the composite material with a golden appearance is arranged on the surface of the main body material.
8. A method for preparing a composite material that maintains the golden appearance of basalt fiber, characterized in that: The following steps are involved: Step 1: Laying a thermoplastic material on the surface of the basalt fiber material for hot pressing and compounding to prepare a basalt golden appearance layer with a golden appearance; Step 2: Lay a bonding medium layer on one surface of the obtained basalt golden appearance layer, and then perform hot pressing and lamination to obtain the composite material with golden appearance.
9. A method for preparing a composite material that maintains the golden appearance of basalt fiber, characterized in that: The composite material according to any one of claims 1 to 6 is laid on a base material on one side with a bonding medium layer and subjected to hot pressing and lamination to obtain the composite material.
10. A composite material according to any one of claims 1 to 6, characterized in that: Used in the field of automotive interior parts or luggage materials.
Citation Information
Patent Citations
Basalt fiber anti-discoloration water-based paint, preparation method and basalt fiber product
CN117344554A
Continuous aramid fiber-basalt fiber second twist fiber reinforced thermoplastic resin prepreg tape and preparation method thereof
CN107245229A
Silica aerogel-nanofiber composite membrane and preparation method thereof
CN116023115A
Thermoplastic resin pellet reinforced with basalt filament
JP2007284631A
Polymer composites comprising an aliphatic polyamide matrix and sized glass or basalt fibres
WO2020099685A1